Misuse of the term `load` in sport and exercise science - Staunton, C. A.; Abt, G.; Weaving, D.; Wundersitz, D. W. T. (Journal of Science and Medicine in Sport, 2022)
Despite the International System of Units (SI), as well as several publications guiding researchers on correct use of terminology, there continues to be widespread misuse of mechanical terms such as `work` in sport and exercise science. A growing concern is the misuse of the term `load`. Terms such as `training load` and `PlayerLoad` are popular in sport and exercise science vernacular. However, a `load` is a mechanical variable which, when used appropriately, describes a force and therefore should be accompanied with the SI-derived unit of the newton (N). It is tempting to accept popular terms and nomenclature as scientific. However, scientists are obliged to abide by the SI and must pay close attention to scientific constructs. This communication presents a critical reflection on the use of the term `load` in sport and exercise science. We present ways in which the use of this term breaches principles of science and provide practical solutions for ongoing use in research and practice.